An analysis of corporate entrepreneurship in the performance of Zimbabwean banks (2010-2012) - Chiyoka, Aylwin (Midlands State University, 2018)
The major focus of the study was to assess the role corporate entrepreneurship has played in the performance of Zimbabwean banks post dollarization (2010-2012). The multicurrency regime brought challenges to banks, which included limited foreign currency reserves, limited capital sources, illiquidity, limited market, market scepticism, and competition that has a bearing on the performance of banks. These challenges have resulted in loss of business for some banks and cases of bank closure. Further, the future attractiveness of the banking industry is doubtful as banks are operating in a mature industry and confronted by an unstable macro environment. The study, thus, sought to explore whether corporate entrepreneurship was playing a role in the performance of banks. The study adopted both the positivism and phenomenological approach where a descriptive survey was considered. The study considered top and middle management from CBZ, Ecobank and NMB, where a sample of 120 was considered representing a true representation of thoughts regarding the topic. Stratified random sampling was used in the selection of these respondents and they were all given a questionnaire. Three follow up interviews top management personnel from these banks was done, with each bank represented. The study noted that banks were not effectively doing new business venturing, innovation, self renewal, acquiring necessary resources, profit seeking activities and conducting risk taking in their CE approaches. The study noted corporate entrepreneurship plays a role in corporate performance through the expansion of existing markets, entering new markets and bringing new products to the existing markets. Some banking industry players were failing to improve their market share and profits through the implementation of CE approaches. The study noted the need for banks to consider technological opportunities, changing customer demands, environment scanning and entrepreneurship culture. The study only focused on the banking sector of Zimbabwe, with very limited focus on other the whole financial industry. Researches on CE within the context of economies like Zimbabwe are developing; hence, more researches on this area should be considered especially with reference to the role of level of management in promoting CE.